The Investigations Required Before Referring a Patient to a Gynaecologic Oncologist. Issue 11 (November 2016) - Kupets, Rachel; Christopher Giede, K.; Power, Patti; Agrawal, Anita
Abstract : (Abstracted from J Obstet Gynaecol Can 2016;38:164–167) The majority of women who develop gynecologic malignancies initially present to family physicians or generalist obstetrician-gynecologists before referral to gynecologic oncologists. Nonsubspecialists may order a number of investigative procedures prior to referral of women with suspected gynecologic cancers.